Nurses' experiences of ethical responsibility: A hermeneutic phenomenological design. (March 2021) - Tollefsen, Annette Strand; Olsen, Aid Bredal; Clancy, Anne
There is a lack of studies on ethical responsibility in nursing. Nurses experience ethical responsibility in all settings where patients are exposed and vulnerable. The authors' interest in public health and intensive care nursing provided a motivation to study these settings. The study aimed to explore how intensive care and public health nurses experience ethical responsibility. A qualitative design was chosen and 10 individual interviews were carried out. The data were analysed using hermeneutic phenomenological analysis. The study is reported in accordance with COREQ. Levinasian ethics provided the theoretical framework. The analysis resulted in four themes: Feeling alone, Feeling worried and uncertain, A sense of satisfaction, A personal commitment . Even though the settings differed, experiences of aspects of ethical responsibility were the same. Further in-depth studies in different settings can enhance an understanding of moral responsibility and facilitate the development of a theory of ethical responsibility in nursing practice.